Pengaruh Kualitas Pelayanan, Persepsi Harga, Dan Lokasi Terhadap Kepuasan Konsumen Pasar Kemiri Muka Di Kelurahan Kemiri Muka - Virhan Arief Fadhila; Suadi Sapta Putra; Kumba Digdowiseiso (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine the effect of service quality, price perception and location on consumer satisfaction in the Kemiri Muka market, Kemiri Muka village. The population in this study used Anderson's sampling technique where the population taken was 100 people with a significance level of 95% and a standard deviation of 25%. This study uses primary data with data collection methods through questionnaires distributed to 100 respondents. The data analysis technique uses inferential analysis with multiple linear regression and uses the Statistical Product and Service Solution (SPSS) version 26.0 program. The results showed that service quality had a positive and significant effect on consumer satisfaction with a path coefficient value of 0.263 and a significant t of 0.015. Price perception has a positive and significant effect on consumer satisfaction with a path coefficient value of 0.216 and a significant t of 0.018. location has a positive and significant effect on consumer satisfaction with a path coefficient value of 0.302 and a significant t of 0.009. Keywords: Service Quality, Price Perception, Location and Consumer Satisfaction